(untitled) (Medico Legal Update, 2021)
Hundred samples were collected from different clinical source. Sixty isolates were identified as Staphylococcus aureus. The ability of S. aureus to produce DNase was examined phenotypically on DNase agar medium and also by quantitative assay that revealed only 37(66%) of S. aureus were able to produce the enzyme. DNase was extracted, the crude activity and specific activity was 38 (U/ml) and 253.3(U/mg) respectively. The enzyme purified by precipitating with ammonium sulphate at (65-85 %) saturation then by using ion exchange chromatography in CM cellulose and gel filtration by using Sephadex G150. Purified DNase activity and specific activity was 42 (U/ml) and 4200(U/mg) respectively. The optimum PH for DNase was found to be 8 while the enzyme was stable at wide range of pH (8, 9 and 10) with remaining activity 100%, 90%, 86% respectively. The optimum temperature for DNase was 37 ºC while the stability was also at 37 ºC. Results indicate that DNase activity increased when the enzyme was incubated with 10 mM of each MnCl2, KCl, NaCl, MgCl2, and CaCl2. The molecular weight of DNase was done by gel filtration and found to be approximately 19KDa.